The Techniques/Methods Used by School Psychologists to Assess Children with Emotional and Behavioural Difficulties - Gadour, Abdelbasit (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2009)
The main aim of this research was to investigate the current methods used by the Libyan school psychologists for children referred to them as having emotional and behavioural difficulties (EBD), and to make comparisons, where possible, with previous research. The data presented is taken from an adapted questionnaire which was based closely on that of McCall (1993). Analysis of responses from 8 schools from the two main Libyan cities (Tripoli & Benghazi) indicated that traditional methods are in common usage among school psychologists. Intelligent tests e.g. attainment and reading tests were used more than observation assessing the children referred. Family factors were found to be the main causes of producing behavioural problems e.g. the dynamics of relationships within the family. The greater number of children referred were found at the primary level with a larger number of boys than girls. The outcome showed tendency among teachers to remove EBD children from the main setting, though their difficulties are learning based.